2021
DOI: 10.3390/biomedicines9070751
|View full text |Cite
|
Sign up to set email alerts
|

AKT Signaling Modifies the Balance between Cell Proliferation and Migration in Neural Crest Cells from Patients Affected with Bosma Arhinia and Microphthalmia Syndrome

Abstract: Over the recent years, the SMCHD1 (Structural Maintenance of Chromosome flexible Hinge Domain Containing 1) chromatin-associated factor has triggered increasing interest after the identification of variants in three rare and unrelated diseases, type 2 Facio Scapulo Humeral Dystrophy (FSHD2), Bosma Arhinia and Microphthalmia Syndrome (BAMS), and the more recently isolated hypogonadotrophic hypogonadism (IHH) combined pituitary hormone deficiency (CPHD) and septo-optic dysplasia (SOD). However, it remains unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The pleiotropic impact of SMCHD1 variants or haploinsu ciency remains a key question to understand how variants in the same gene might lead to at least four different syndromes, 4,15,[17][18][19] in which D4Z4 hypomethylation but also DUX4 expression are consistently observed 17,18,35,[41][42][43] . In FSHD2, SMCHD1 variants were previously located around the ATP binding site or on a loop adjacent to the ATP binding pocket 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The pleiotropic impact of SMCHD1 variants or haploinsu ciency remains a key question to understand how variants in the same gene might lead to at least four different syndromes, 4,15,[17][18][19] in which D4Z4 hypomethylation but also DUX4 expression are consistently observed 17,18,35,[41][42][43] . In FSHD2, SMCHD1 variants were previously located around the ATP binding site or on a loop adjacent to the ATP binding pocket 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, and despite D4Z4 hypomethylation in SMCHD1 KO NCC, DUX4 was not induced in SMCHD1 KO NCC. Notably, a recent study of NCC derived from one arhinia patient iPSC and one control iPSC also failed to demonstrate DUX4 induction in arhinia NCC but suggested that there may be a very mild defect in arhinia NCC migration related to diminished AKT signaling ( 46 ). Thus, while the primary defect in arhinia appears to be placodal, placode cell death may impair the proliferation and/or migration of nearby NCC such that a combined defect prevents the development of the human nose.…”
Section: Discussionmentioning
confidence: 99%
“…Gene Set Enrichment Analysis (GSEA) was performed on all genes expressed. RNA seq methods in primary fibroblast are described in Laberthionniere et al 38 .…”
Section: Discussionmentioning
confidence: 99%